Dampak Peningkatan Kesejahteraan Guru terhadap Mutu Peminat - Rumtini -- (Jurnal Pendidikan dan Kebudayaan, 2014)
This study is aimed to provide better policy recommendations related to theÂ government efforts in encouraging high schools graduations with high academic achievementÂ to enroll teacher training institutes. Study used data from the impact evaluation of the teachersÂ living standards improvement on the quality of input. The overview were aimed to measure theÂ extent of which high school graduaters enrolled to teachersâ€™ colleges. Survei approach wasÂ implemented to collect data from the two sources, Student Administration Bureau and studentsÂ of 1st, 3rd, 5th, and 7th by 2011. Findings showed that there were increasing sharfly numbersÂ of enrollements to teachersâ€™ colleges during 2008-2011, especially for primary school teachersÂ program. However, in term of quality, there were only slightly increased on quality of teachersâ€™Â candidate shown by the slight increase of high schoolsâ€™ studentsâ€™ rank of those who were in theÂ 7th semester compared to 1st semester. Policy options will be: only high quality teacher trainingÂ insitute are eligible to open the program; high knowledgeable and skills on curriculum contentÂ and pedagogic; student loan scheme; hiring teachrs of both local and outside with centralizedÂ teacher management; teachersâ€™ contract for the remote, border, and outer areas.Â ABSTRAKÂ Penelitian bertujuan merumuskan saran kebijakan dalam upaya peningkatan peminatÂ profesi guru berkualitas pada Lembaga Penghasil Tenaga Kependidikan. Penelitian difokuskanÂ pada kuantitas dan kualitas lulusan sekolah lanjutan tingkat atas yang mendaftar pada beberapaÂ prodi pendidikan. Melalui survei, informasi dikumpulkan dari dua sumber data, yaitu BadanÂ Administrasi Kemahasiswaan dan mahasiswa prodi kependidikan dan non-prodi kependidikan,Â khususnya semester 1, 3, 5, dan 7 pada tahun 2011. Hasil penelitian menunjukkan bahwa terdapatÂ peningkatan kuantitas dan kualitas peminat profesi guru khususnya mahasiswaÂ kependidikan. Secara kuantitas, terjadi peningkatan tajam jumlah pendaftar kependidikanÂ terutama prodi Pendidikan Guru Sekolah Dasar. Pada sisi kualitas, terdapat peningkatan lebihÂ baik ranking ketika di sekolah lanjutan tingkat atas pada sebagian mahasiswa semester awalÂ dibandingkan mahasiswa semester akhir, meskipun mayoritas mahasiswa kependidikan masihÂ berasal dari mereka yang memiliki ranking bawah ketika di sekolah lanjutan tingkat atas.Â Beberapa opsi kebijakan antara lain: perlunya pengetatan perizinan pendirian LPTKÂ mengedepankan kriteria â€œmutuâ€; persyaratan ketat terhadap penguasaan konten dan pedagogis;Â pemberlakukan skema kredit mahasiswa; peluang guru selain dari unsur daerah, dibuka peluangÂ guru dari wilayah Jawa dengan pengelolaan terpusat; memberlakukan guru kontrak dari wilayahÂ Jawa ke wilayah 3T (terdepan, terluar, dan terpencil).